EDUKASI KONSEP AKUNTANSI HIJAU UNTUK USAHA BERKELANJUTAN DENGAN PEMANFAATAN LIMBAH DI DESA MEKAR MANIK KECAMATAN CIMENYAN KABUPATEN BANDUNG - Irene Sukma Lestari Barus; Apriwandi Apriwandi; Debbie Christine; Syakieb Arsalan; Kartika Wulandari (Buletin Ilmiah Nagari Membangun, 2024)
This study aims to introduce and analyze the application of green accounting principles in sustainable business practices, particularly through the utilization of organic waste as a strategy to support environmental sustainability and economic development. Employing a qualitative descriptive approach, the study involved Focus Group Discussions (FGDs) and in-depth interviews with small business owners in Mekarmanik Village, Bandung, alongside field observations to gain insights into the benefits of green accounting. Findings indicate that implementing green accounting not only enhances operational efficiency through improved waste management and resource savings but also generates new economic opportunities by converting waste into value-added products, such as organic fertilizers and alternative raw materials. This approach strengthens the competitive edge and capacity of small businesses to grow sustainably while preserving environmental balance. Furthermore, the program has successfully raised awareness among small businesses about waste processing, leading to the creation of economically valuable products, improved agricultural productivity, and enhanced public health and well-being, in alignment with the Sustainable Development Goals (SDGs). Additionally, business owners recognized that this initiative supports government efforts in poverty alleviation, hunger reduction, and the production of natural, healthy products. Recommendations from this study include ongoing monitoring by community engagement teams to ensure consistency in waste recycling practices, provision of land for waste management for businesses demonstrating success in waste processing, expansion of the program to sectors beyond agriculture, and encouragement for local governments to activate Women Farmers’ Groups (KWT) as centers for enterprise development and organic waste processing.